1996
DOI: 10.1007/bf01403704
|View full text |Cite
|
Sign up to set email alerts
|

MR of the pituitary in patients with Prader-Willi syndrome: Size determination and imaging findings

Abstract: Prader-Willi syndrome (PWS) is an unusual genetic disorder characterized by short stature, obesity, hypogonadism, hypotonia, cognitive impairment, and dysmorphic facies. There is an interstitial deletion of the proximal long arm of chromosome 15 in about 70 % of patients. Some of these clinical features suggest a central hypothalamic/pituitary dysfunction, and recent investigations have demonstrated a marked impairment in spontaneous growth hormone (GH) secretion. We studied 15 GH-deficient PWS patients by mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 16 publications
(15 reference statements)
2
22
0
2
Order By: Relevance
“…We performed pituitary MRI in 16 patients and found pituitary hypoplasia in more than 60% of them whatever their GH status. This pituitary defect has already been reported in patients with PWS with the same incidence [25, 26]. Here we show that pituitary hypoplasia is not related to GHD, but rather to the syndrome itself.…”
Section: Discussionsupporting
confidence: 59%
“…We performed pituitary MRI in 16 patients and found pituitary hypoplasia in more than 60% of them whatever their GH status. This pituitary defect has already been reported in patients with PWS with the same incidence [25, 26]. Here we show that pituitary hypoplasia is not related to GHD, but rather to the syndrome itself.…”
Section: Discussionsupporting
confidence: 59%
“…Studies of pituitary size and structure are limited and contradictory. One study reports no significant difference in height of the anterior pituitary lobe in growth hormone-deficient PWS individuals compared with normal controls or children with isolated growth hormone deficiency (GHD) [6]. In two other studies, however, a reduction of pituitary height was observed in 50–60% of the patients with PWS [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Structural abnormalities of the brain documented in PWS include frequent ventriculomegaly and cortical abnormalities. Pituitary abnormalities are common, but structural abnormalities of the hypothalamus are not typically found (1)(2)(3). Children with PWS typically have decreased spontaneous GH secretion and low peak GH response in stimulation tests (4,5), accompanied by reduced serum IGF-I and low IGF-binding protein 3 (6 -8).…”
mentioning
confidence: 99%